Combustion behavior and thermal analysis of agricultural and woody biomass blends - Harun, N.Y. (American-Eurasian Network for Scientific Information, 2015)
Background: Blended biomass, a new feedstock for pellets production potentially be viable to support the demand for wood pellets at present and in the future. Combustion behavior and characteristics tests were carried out in thermogravimetry (TG) analyzer with an air flow rate of 100 ml/min and heating rate of 20 Â°C/min. Heat flow and heat required for the biomass reaction was measured using differential scanning calorimeter (DSC). Objective: The purpose of this study was to investigate the combustion behaviour and thermal properties of both individual and blend agricultural (reed canary grass, timothy hay and switchgrass) and forestry biomass (spruce and pine). Results: The TG results showed that the combustion behavior of all the biomass samples including the blends were almost similar. Two main stages of combustion reaction were presented by differential thermal analysis (DTA) curve. The heat released from the blended biomass (6.94 â 9.26 kJ/kg) was higher than the individual agricultural biomass (4.59 â 6.78 kJ/kg) but lower than individual spruce (10.2kJ/kg) and pine (11.13kJ/kg). Conclusion: The findings indicate that the reactivity of the individual agricultural biomass material changed due to blending. Overall, blending can help to increase the energy capacity and can improve the combustion characteristics. Â© 2015 AENSI Publisher All rights reserved.